Systematic review: Pharmacological treatment of tic disorders – Efficacy of antipsychotic and alpha-2 adrenergic agonist agents - Weisman, Hannah; Qureshi, Imraan A.; Leckman, James F.; Scahill, Lawrence; Bloch, Michael H. (Neuroscience and biobehavioral reviews, 2013)
We conducted a meta-analysis of randomized, placebo-controlled trials to determine the efficacy of antipsychotic and alpha-2 agonists in the treatment of chronic tic disorders and examine moderators of treatment effect. Meta-analysis demonstrated a significant benefit of antipsychotics compared to placebo (standardized mean difference (SMD)=0.58 (95% confidence interval (CI): 0.36-0.80). Stratified subgroup analysis found no significant difference in the efficacy of the 4 antipsychotic agents tested (risperidone, pimozide, haloperidol and ziprasidone). Meta-analysis also demonstrated a benefit of alpha-2 agonists compared to placebo (SMD=0.31 (95% confidence interval CI: 0.15-0.48). Stratified subgroup analysis and meta-regression demonstrated a significant moderating effect of co-occurring ADHD. Trials which enrolled subjects with tics and ADHD demonstrated a medium-to-large effect (SMD=0.68 (95%CI: 0.36-1.01) whereas trials that excluded subjects with ADHD demonstrated a small, non-significant benefit (SMD=0.15 (95%CI: -0.06 to 0.36). Our findings demonstrated significant benefit of both antipsychotics and alpha-2 agonists in treating tics but suggest alpha-2 agonists may have minimal benefit in tic patients without ADHD.